Development of an experimental construction of a device for cleaning from small piece of contaminants - Obidov, Avazbek; Akhmadalieva , Dilnoza; Otaqoʻziyev , Doniyorjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the results of the work on the creation of the experimental construction of the improved small dirt cleaning device and conducting experiments on it are given. As a result of this research, an improved scheme of arrangement of working bodies and an effective mode of operation of the device for cleaning cotton from small piece of contaminants was developed.